Construction and cloning of synthetic M2e-NP gene from asian influenza a viruses - Seng, Teh Yew (2013)
The sudden emergence and explosive spreading of novel influenza A viruses in the community represents a major threat to global public health. Conventional influenza vaccines are mainly targeting two surface glycoproteins namely hemagglutinin (HA) and neuraminidase (NA) that undergo antigenic drift and antigenic shift continuously. This poses extraordinary challenges to the virologist for strain identification and effective vaccine preparation during a pandemic. Hence, there is a pressing need to develop an effective universal vaccine that can confer immediate protection against different variants and subtypes of influenza A viruses. In recent years, nucleoprotein (NP) and extracellular domain of ion channel matrix protein (M2e) have been widely targeted as possible universal vaccine candidates since these two proteins are highly conserved among all influenza A viruses. In this study, we aimed to construct, amplify and clone synthetic M2e-NP gene that can serve as universal influenza vaccine in future. This study comprises of two major parts. First part involves in silico analysis of M2e and NP amino acid sequence from 24 subtypes and variants of Asian influenza A viruses in order to identify conserved and immunogenic peptide sequences. In second part, II newly synthesized oligonucleotides with length ranged from 32-38 bp were assembled and amplified using Taq DNA polymerase in assembly PCR. Subsequently, PCR products were ligated into the pCR®2.1-TOPO® vector followed by transformation into the E. coli DH5a competent cells. Few white colonies were selected and screened via colony PCR. Then, recombinant plasmids that harboured desired insert were extracted from positive clone and subjected to restriction enzyme digestion using Hindlll and Xhol to verify the presence of the insert prior to sequencing. In the present study, we had successfully constructed and cloned synthetic M2e-NP gene. Target band with size